1996
DOI: 10.1063/1.117754
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of soft x-ray pulse emitted from aluminum plasma produced by a pair of Ti:sapphire laser pulses

Abstract: The temporal and spectral evolution of soft x-ray pulses (40–100 Å) emitted from Al plasma produced by a pair of femtosecond Ti:sapphire laser pulses at normal incidence was studied. Both the soft x-ray emission and the pulse duration increased with increase in the scale length of the preformed plasma. Prepulse enhanced soft x-ray emission about 100 times with a pulse duration of 100–130 ps. A spectrally resolved time history revealed that the emission at shorter wavelengths started and decayed relatively more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…Pre-plasma formation has been investigated in detail as one of the prominent ways of improving the x-ray yields. While significant enhancement in the emission is noticed, the x-ray pulse duration tends to become longer in such cases [11,12]. There is increasing interest on the role of modulation/roughness of the surface in increasing the coupling of the input light into the plasma, which results in an enhancement in the x-ray yield.…”
mentioning
confidence: 99%
“…Pre-plasma formation has been investigated in detail as one of the prominent ways of improving the x-ray yields. While significant enhancement in the emission is noticed, the x-ray pulse duration tends to become longer in such cases [11,12]. There is increasing interest on the role of modulation/roughness of the surface in increasing the coupling of the input light into the plasma, which results in an enhancement in the x-ray yield.…”
mentioning
confidence: 99%
“…Preplasma formation has been investigated in detail as one of the prominent ways of improving the x-ray yields [29]. While significant enhancement in the emission is noticed, it has also been shown that the x-ray pulse duration tends to become longer in such cases [30,31]. The role of modulation/roughness of the surface in increasing the coupling of the input light into the plasma, which results in an enhancement in the x-ray yield, has been studied in detail.…”
Section: Pioneering Work On Ultrafast Plasmasmentioning
confidence: 99%
“…[3][4][5][6][7][8] We have observed an enhancement of 100 times in soft x-ray emission using this scheme. 6,8,9 The low-density plasma created by the prepulse not only increased the light absorption, but also broadened the pulse duration in the soft x-ray region to more than 100 ps. 8,9 Another way to increase the light absorption is the use of structured target such as grating and porous.…”
mentioning
confidence: 99%
“…6,8,9 The low-density plasma created by the prepulse not only increased the light absorption, but also broadened the pulse duration in the soft x-ray region to more than 100 ps. 8,9 Another way to increase the light absorption is the use of structured target such as grating and porous. [10][11][12] Recently, quartz and other insulators were reported to show higher absorption of ultrashort laser pulses at low laser intensities ͑10 13 -10 15 W/cm 2 at 400 nm͒.…”
mentioning
confidence: 99%
See 1 more Smart Citation